Islamic Moderation in Higher Education - Rusli, Ris’an; Muchtar, Aflatun; Afriyanto, Afriyanto (Opción, 2019)
Globalization era is the era of ‘diplomacy’, an era in which Muslims are re- quired to be moderate (wasathiyah). Muslims as moderates’ people must be able to integrate two different dimensions; dimensions ‘theocentric’ (hablun min Allah) and ‘anthropocentric’ (hablun min an-nas). These demands are not demands of the times, but demands of the Qur’an that must be implemented. The meaning of the wasathiyah should not be taken from the understanding of the extremists who tend to put forward a hard attitude without compromise (ifrâth), or the understanding of liberal groups who often interpret religious teachings in a very loose, free, even almost leaving the line of religious truth (tafrîth). The meaning of Islam as wasathiyah religion must be taken from the explanations of the scholars, so as not to trigger ‘misunderstanding’ and intol- erant attitudes that damage the image of Islam itself. The right understanding of wasathiyah is able to form a conscious attitude in moderate Islam in the true meaning (ummatan wasathan), to realize world peace, without violence in the name of groups, races, ideologies and even religions.